Recent advances in cost-effective aluminum alloys with enhanced mechanical performance for high-temperature applications: A review - Liying Cui; Kun Liu; X.-Grant Chen (Materials & Design)
Developing aluminum alloys with excellent high-temperature (HT) mechanical performance is imperative for advancing a low-carbon, energy-efficient society. Over the past decade, research on the development of Al alloys for HT applications has significantly intensified. Key mechanical properties such as strength, creep resistance, and fatigue performance are critical for Al alloys operating above 250 °C. This review evaluates recent cost-effective innovations and outlines several design strategies for optimizing these properties, which includes the selection of heat-resistant precipitates, microalloying, and incorporating intermetallic compounds. The effectiveness of these approaches can vary significantly depending on Al systems. Improvements in mechanical performance across diverse systems, specifically Al-Cu, Al-Mn, Al-Mg, Al-Mg-Si, and Al–Si, has been critically reviewed. Precipitation strengthening remains the predominant approach for improving HT mechanical properties. Microalloying is proven to be an effective approach for facilitating the formation of fine and stable precipitates. The evolution of the mechanical properties at the HT of numerous alloys under various approaches, including strength, creep and fatigue properties, has been summarized. Although extensive research has been conducted for optimizing the microstructure and mechanical attributes, there remains considerable potential for further advancements in the HT performance of Al alloys, which can lead to breakthroughs in various industrial applications.